Diversity of myxobacteria isolated from Weizhou Island, Guangxi, and their potential biological activities - Meng Kangting; Jiang Wang; Cai Huimin; Yang Zhaoming; Yuan Yiran; Su Zhiwei (Archives of Biological Sciences, 2025)
This study investigated the diversity of cultivable marine myxobacteria from Weizhou Island in the Beibu Gulf of Guangxi, with a particular focus on strains exhibiting potential antibacterial activity and associated enzyme production. The Escherichia coli entrapment method and filter paper methods were employed for separation, followed by purification using sequential conversion techniques. Myxobacteria were identified through morphology characterization and 16S rRNA gene sequence analyses. The antibacterial activity against porcine pathogens was assessed using the plate confrontation method, and enzyme activity was evaluated through the plate assay method. From 13 island samples, 28 myxobacteria cultures were isolated, representing 13 species across 8 genera, predominantly Myxococcus. The antibacterial test showed remarkable activity in 9 myxobacteria strains. Cystobacter fuscus (GXIMD 01665c) and Myxococcus virescens (GXIMD 01661b) produced inhibition zones of 54.4±0.18 mm and 57.33±0.09 mm against E. coli L2 and E. coli 10, respectively. The enzyme activity experiment revealed that all 9 strains of myxobacteria could produce protease and cellulase, with 7 strains specifically producing chitinase, 6 strains producing amylase, and 4 producing lipase. These findings highlight the diverse antibacterial properties and enzymatic potential of myxobacteria from Weizhou Island. Strains GXIMD 01665c and GXIMD 01661b emerged as valuable microbial resources, holding great promise for further research and development.